2020
DOI: 10.1159/000506825
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Prasugrel in Elderly/Low Body Weight Japanese Patients with Ischemic Stroke: Randomized PRASTRO-II

Abstract: Introduction: The safety of prasugrel in elderly and/or low body weight Japanese patients with ischemic stroke who have a relatively high bleeding risk with antiplatelet therapy remains unknown. Objective: We aimed to investigate the safety and efficacy of long-term prasugrel monotherapy for stroke prevention compared with clopidogrel in elderly and/ or low body weight Japanese patients with non-cardioembolic ischemic stroke. Methods: In this randomized, doubleblind, comparative, phase III study, elderly (age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…This suggests that in high-risk patients, the event rate of ischemic stroke recurrence is likely to be lower with prasugrel than with clopidogrel. Overall, since the number of cases in this study was small, it is necessary to consider these results together with those of PRASTRO-I and PRASTRO-II 6,7,10) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that in high-risk patients, the event rate of ischemic stroke recurrence is likely to be lower with prasugrel than with clopidogrel. Overall, since the number of cases in this study was small, it is necessary to consider these results together with those of PRASTRO-I and PRASTRO-II 6,7,10) .…”
Section: Discussionmentioning
confidence: 99%
“…Prasugrel has been approved in Europe, the US, and Japan for the treatment of patients with heart disease who have undergone percutaneous coronary intervention [3][4][5] . In the field of cerebrovascular medicine, the efficacy and safety of prasugrel have been demonstrated in two multicenter, double-blind, comparative studies (PRASTRO-I, PRASTRO-II) conducted in patients with non-cardioembolic stroke in Japan 6, 7) .…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have investigated alternatives to clopidogrel. A Japanese study found that prasugrel and clopidogrel were equally effective at preventing vascular events in non-cardioembolic stroke patients [ 27 , 28 ]. A Chinese study found that ticagrelor plus aspirin treated patients with transient ischaemic attack (TIA) or minor stroke had lower platelet activity than those treated with clopidogrel, especially CYP2C19 LoFA carriers [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PRASTRO-II study investigated 2 different doses of prasugrel (2.5 mg/day or 3.75 mg/day) versus clopidogrel (50 mg/day) in Japanese patients aged ≥75 and weighing ≤50 kg) and found no significant differences in the rates of ischemic stroke, myocardial infarction, vascular death, or major bleeding. 47 As such, there is not enough evidence to support the use of prasugrel instead of using clopidogrel in individuals with a history of ischemic stroke or TIA.…”
Section: Antiplatelet Drugsmentioning
confidence: 99%